Physical properties of nanocomposites prepared by in situ polymerization of high-density polyethylene on multiwalled carbon nanotubes - Kim, Jihun; Hong, Soon Man; Kwak, Soonjong; Seo, Yongsok (ROYAL SOC CHEMISTRY, 2009)
In situ metallocence polymerization was used to prepare nanocomposites of multiwalled carbon nanotubes (MWCNT) and high density polyethylene (HDPE). This polymerization method consists of attaching a metallocene catalyst complex onto the surface of MWCNT followed by surface-initiated polymerization to generate polymer brushes on the surface. All the procedures of polymerization made progress with one-pot process. The morphological observation of nanocomposites using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that the nanotubes are uniformly dispersed throughout HDPE matrix. Physical properties of thermal and electrical conductivities and rheological response have been characterized. Since the carbon nanotubes are wrapped by PE molecules, the large interface provided by MWCNT's lead to strong phonon boundary scattering. Thus, the enhancement of thermal conductivity by the inclusion of nanotubes was quite restrictive. On the other hand, electrical conductivity and rheological properties show the property transition at the critical concentration of carbon nanotubes (percolation threshold). The DC conductivity increased with increasing weight fraction of MWCNT from 1.0 x 10(-13) S cm(-1) (neat HDPE) to 1.3 x 10(-2) S cm(-1) (HDPE/7.3 wt% of MWCNT) at room temperature and the electrical percolation threshold was ca. 7.3 wt%. The percolation threshold concentration of MWCNT for the rheological properties was ca. 8.7 wt%, similar to that of the electrical conductivity. Difference in the percolation behaviors between the MWCNT mixed nanocomposites and the PE-coated MWCNT nanocomposites is discussed in terms of the dispersion and the tube-tube distance of MWCNT.
Keywords: MECHANICAL-PROPERTIES; THERMAL-CONDUCTIVITY; CRYSTALLIZATION